HUBUNGAN MOTIVASI RELIGIUS DENGAN PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK - Amin, Muhammad (Universitas Islam Negeri Alauddin Makassar, 2020)
One of the main benchmarks for perceiving the triumph of learning of student is by beholding the extent to which learning achievements are attained. Learning achievement is the degree to which student’s knowledge of the given material is received.This study focuses on the extent to which religious motivation of the students relates to their learning achievements. Data were obtained by using a questionnaire. The subjects of this study were 116 students of Madrasah Aliyah Negeri 1 Makassar. The data were analyze with descriptive correlational analysis.The result of this study indicates a significant relationship between religious motivation and student achievements. There is 0,233 of correlation coefficient with a significance of 0,001. Hypothesis was tested by comparing the significance level (p-value)with matrix that if the significance is 0,05 then Ho is accepted, if significance <0,05, then Ho is rejected and Ha is accepted. In this case, it could be seen that there is 0,233 of the correlation coefficient with 0,001 if significance. Owing to that significance which is <0.05 then Ho is rejected and Ha is accepted.